The South Carolina Encyclopedia Guide to South Carolina Writers - Mack, Tom (Book collections on Project MUSE., 2014)
"The South Carolina Encyclopedia Guide to South Carolina Writers expands the range of writers included in the landmark South Carolina Encyclopedia. This guide updates the entries on writers featured in the original encyclopedia and augments that list substantially with dozens of new essays on additional authors from the late eighteenth century to the present who have contributed to the Palmetto State's distinctive literary heritage. Each profile in this concise reference includes essential biographical facts and critical assessments to place the featured writers in the larger context of South Carolina's literary tradition. The guide comprises 127 entries written by more than seventy literary scholars, and it also highlights the sixty-five writers inducted thus far into the South Carolina Academy of Authors, which serves as the state's literary hall of fame. Rich in natural beauty and historic complexity, South Carolina has long been a source of inspiration for writers. The talented novelists, essayists, poets, playwrights, journalists, historians, and other writers featured here represent the countless anonymous individuals who have shared tales and lore of South Carolina"--